MOTIVASI SUNNI AXIS MEMBANTU HARAKAH AHRAR SYAM Al ISLAMIYYAH DALAM KONFLIK SURIAH (2015-2016) - Bambang Putra Ermansyah; Tri Joko Waluyo (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
Syria is one of the countries affected by a wave of revolution demanding changes in the Middle East region, or commonly known as the Arab Spring. Among those countries, Syria is a country with the highest complexity and escalation of conflicts among other affected countries. Many emerging actors who have their own interests in this conflict, both domestic and international actors, including those who will be discussed in this study are the Sunni Axis and Harakah Ahrar Syam Al Islamiyyah.             This research will discuss the motivation of Sunni Axis countries led by Saudi Arabia to support the rebel group named Harakah Ahrar Syam Islamiyyah and various forms of support assistance in the 2015-2016 Syrian War. This research using the perspective of Constructivism with Securitization and Regional Security Complex Theory and the level analysis of this research is Nation State. This research uses library research as a data collection method and focusing at the motivation of Sunni Axis states that support Harakah Ahrar Syam Al Islamiyyah.             Researcher have found that Sunni Axis states are supporting the Harakah Ahrar Syam Al Islamiyyah as a means against Iran’s influences in the region with financial, arms, and political support.